2017
DOI: 10.1371/journal.pone.0176522
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and extent of heteroresistance by next generation sequencing of multidrug-resistant tuberculosis

Abstract: Amplicon-based Next Generation Sequencing (NGS) is an emerging method for Mycobacterium tuberculosis drug susceptibility testing (DST) but has not been well described. We examined 158 clinical multidrug-resistant M. tuberculosis isolates via NGS of 11 resistance-associated gene regions covering 3519 nucleotides. Across these gene regions, complete resistance or heteroresistance (defined as 1%-99% mutation) was present in at least one isolate in 6.3% of loci. The number of isolates with heteroresistance was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 28 publications
2
46
1
Order By: Relevance
“…Other explanations for the occurrence of heterogeneous clusters can be discussed, for example, the existence of heteroresistance within M. tuberculosis isolates, i.e., the presence of drug-susceptible and drug-resistant bacteria in the same isolate. Recently, a study investigating the prevalence of heteroresistance by WGS showed that for around 50% of the isolates tested, heteroresistance was present in at least one resistance-associated genomic locus (24). Moreover, the existence of resistant minority subpopulations in M. tuberculosis was described previously (25).…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations for the occurrence of heterogeneous clusters can be discussed, for example, the existence of heteroresistance within M. tuberculosis isolates, i.e., the presence of drug-susceptible and drug-resistant bacteria in the same isolate. Recently, a study investigating the prevalence of heteroresistance by WGS showed that for around 50% of the isolates tested, heteroresistance was present in at least one resistance-associated genomic locus (24). Moreover, the existence of resistant minority subpopulations in M. tuberculosis was described previously (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study showed that for RNA Medium and DNA High inputs, additional technical replicates allowed for SNVs to be called at lower percentage frequencies ( Table 2 ) whist maintaining maximum accuracy. In previous studies, where a percentage frequency cut-off has been used to identify SNVs, no consideration for input material or PCR amplification was applied to reduce processed-introduced errors being called as real SNVs [ 8 , 37 , 38 ]. This study highlights the need for a tailored approach to frequency thresholds depending on template input concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of classic Xpert, previous studies report LOD values ranging from 65 to 100% (14, 15), for Ultra, the first validation study conducted by the manufacturer presented LODs only for mutations L430P, H445N (20-40%), and S450L (5-10%) (16), whereas LODs of Genoscholar NTM+MDRTB II have not been reported yet. High coverage depths achieved through pre-selected amplified genes allow targeted deep sequencing to capture and quantify minority resistant variants of Mycobacterium tuberculosis mutants and detect RIF heteroresistance with high sensitivity (17, 18). As an example of such an approach, Deeplex®-MycTB (Genoscreen, France; Deeplex) employs ultra-deep sequencing of a single, 24-plexed amplicon mix to detect drug resistance-associated mutations in M. tuberculosis complex (MTBC) strains, in addition to mycobacterial species identification and MTBC strain genotyping, with a 24-48 turnaround time starting from smear positive clinical samples or primary cultures.…”
Section: Introductionmentioning
confidence: 99%